Pengaruh Kualitas Bahan Baku Dan Proses Produksi Terhadap Efektivitas Produksi Paving Block Di PT. Samson Jaya Utama - Dudi Haryadi (Lembaga Penelitian Universitas Langlangbuana, 2019)
Every company that has a large or small scale is likely to face problems about choosing the best quality of raw materials, so that the implementation of the production process can run effectively in order to get maximum results.This study aims to determine the effect of the quality of raw materials and production processes on the effectiveness of the production of paving blocks in PT. Samson Jaya Utama. In this study using descriptive verification research method using statistical analysis methods, namely path analysis by testing statistical hypotheses partially and simultaneous. Data collected through library studies, observations, interviews and questionnaires. The results of this study indicate that the quality of raw materials and the production process has an influence on the effectiveness of the production of paving blocks in PT. Samson Jaya Utama.